Terapia fonoaudiológica assistida por cães: estudo de casos clínicos - Domingues, Camila Mantovani (2008)
INTRODUCTION: By sharing our routines with animals, they became part of our culture when start to occupy different roles, besides the company. Currently, due to the benefits not restricted to common sense, but also listed from scientific research, they are in clinics, hospitals, schools and many others institutions. These studies gave itself two ways to call procedures involving animals with the purpose of taking care of human health: animal-assisted activities (AAA) and animal-assisted therapy (AAT) (DELTA SOCIETY, 2006) OBJECTIVE:Investigating the possible effects of the interaction speech therapyst-patient-dog in the operation of patients language with disturbances of language. The event set in the possibility of the device animal, in speech therapy setting, enhance the therapeutic process. METHOD: Clinical-quality research, developed in study of clinical cases mode. The ethical standards for research with humans and animals were obey.Casuistry: Three subjects, from sample unintentional: Jonas, 12; 0 years, male, with difficulties in writing / reading language; Lucas, 8; 0 years, male with school´s complaints related to difficulties in the written / reading language, summed the dismotivation for learning; Pedro, 4; 0 years, male with phonological changes that lead to segments of unintelligible speech, as well as complaints related to aggressive behavior. The animal participant was a dog without defined race (SDR), seven years old, female, selected in accordance with the criteria proposed by Aiello (DOTTI, 2005). Procedure: The clinical material was recorded in writing regularly and the sessions were recorded on digital camera bimonthly. The interpretation of the data came from theoretical benchmarks of anthropology, speech therapy, psychoanalysis and AAT. RESULTS: The AAT favored the interaction between therapist / patient, intensified the activity dialogical (LaFRANCE et al, 2007) the motivation to write and to read, the reduction of the problems manifest in writing (replacements / omissions grafemics, junction / separation misuse of words); besides mobilize the affectivity of the patients.CONCLUSION: The introduction of AAT as a therapeutic device shown to be effective in clinical cases studied. It is suggested therefore that the Speech Therapy participate more actively in this field of study, since the results corroborate the findings of research that suggests the effectiveness of AAT in various therapeutic environments